Improvement of the Solubility and Dissolution Characteristics of Risperidone via Nanosuspension Formulations - Emad, Hayder; Nazar Abd-Alhammid , Shaimaa (Iraqi Journal of Pharmaceutical Sciences, 2022)
Risperidone is an atypical antipsychotic drug that is used for treating schizophrenia, bipolar mania, and autism. Risperidone rebalances dopamine and serotonin to improve thinking, mood, and behavior by working on dopamine and serotonin α2receptor antagonism. Risperidone has poor solubility and high permeability through the intestine, so it belongs to Biopharmaceutical Classification System (BCS) class II exhibits poor oral biopharmaceutical properties. The aim of the present work was to improve solubility and dissolution of Risperidone by preparing nanosuspension using different stabilizers and different solvents‎ in a method known as solvent-antisolvent precipitation method.  Twenty-eight formulas were prepared and evaluated particle size, PDI, (EE), zeta potential, and in-vitro dissolution studies. The results showed that particle size of nanosuspension was nanosized for all formulations. The best formula (F13) has particle size (40.9) nm containing a (Soluplus) as a stabilizer in ratio 1:1 with drug by using acetone as a solvent in ratio 1:5 with water which was act as anti-solvent with stirring speed 1000 rpm and E.E % was 98%. For self-dispersible dry nanosuspension, the selected formula (F13) shown fast dispersibility of less than 1 min. and complete in-vitro dissolution to about 30 min. in 0.1N HCl. XRD and DSC indicate the transformation of a crystalline form of risperidone into an amorphous form. The stability studies of the best formula (F13) suggest that estimated shelf life was about 4 years.In conclusion; the formulation of poorly water-soluble risperidone as nanosuspension significantly improved the dissolution rate of drug and enhanced its solubility.